Genetic instability in Drosophila melanogaster: deletion induction by insertion sequences. - Green, M.M. (Proceedings of the National Academy of Sciences of the United States of America, 1982)
Females of Drosophila melanogaster heteroallelic or homoallelic for X chromosome giant (gt) mutants generate deletions involving the wild-type alleles at two X chromosome gene loci: yellow body color (y) and white eye color (w). The deletions, bidirectional in the case of y and with fixed endpoint in the case of w, are associated with particular X chromosomes. Distinctive insertion sequences, located proximal to the target loci, are presumed to generate the deletions.